2006
DOI: 10.1007/s11249-005-9012-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental simulation of chemical reactions between ZDDP tribofilms and steel surfaces during friction processes

Abstract: International audienceFriction tests are performed in a controlled environment (Ultra High Vacuum), between steel surfaces and a ZDDP tribofilm at different contact severities. According to AES analyses, evidence of chemical reactions activated by friction is given. The reaction of the ZDDP tribofilm with the native iron oxide could partially explain its antiwear behavior

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
5
23
0
Order By: Relevance
“…The ratio is corrected for the contributions to NBO originating from sulphate groups and carbon bound to oxygen was composed of long-chain poly(thio)phosphates, in agreement with previous work [11,29]. A potential drawback of the oscillating-load test approach is that part of the film formed at high contact pressure might be transferred to areas at low contact pressures [33,34]. However, no evidence for a possible transfer was found and the results are in agreement with results obtained with the constant-load test [11].…”
Section: Comparison Of the Constant-load And Oscillatingload Approachessupporting
confidence: 85%
See 1 more Smart Citation
“…The ratio is corrected for the contributions to NBO originating from sulphate groups and carbon bound to oxygen was composed of long-chain poly(thio)phosphates, in agreement with previous work [11,29]. A potential drawback of the oscillating-load test approach is that part of the film formed at high contact pressure might be transferred to areas at low contact pressures [33,34]. However, no evidence for a possible transfer was found and the results are in agreement with results obtained with the constant-load test [11].…”
Section: Comparison Of the Constant-load And Oscillatingload Approachessupporting
confidence: 85%
“…It has been suggested that during a tribological contact similar reactions occur on the surfaces of both counterparts, starting at room temperature [11,32]. But while it has been proven that the tribofilm changes on the disc as a function of test temperature from a zinc phosphate at low temperature to a zinc polyphosphate at higher temperature [11,20,22,25,26] only very little analysis of the ball has been carried out [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of friction, the lubricants are likely to be contaminated and oxidized to certain extent, which results in corrosion and wear of the rubbing surfaces [4,35]. ZDDP as corrosion inhibitor and antioxidant has aroused scholars' extensive interest and been widely studied; it is the generally-used lubricant additive [36].…”
Section: Corrosion and Electrochemical Testsmentioning
confidence: 99%
“…The composition of the tribological films formed in the presence of ZnDTP is heterogeneous, with longer polyphosphate chain lengths being present in the outermost layer and a layer of shorter-chain-length polyphosphates at the bottom, which also contains zinc, iron, and some sulfur and unreacted/partially reacted additive adsorbed on the surface [8][9][10]44]. Many parameters can influence the composition and the thickness of the tribofilms.…”
Section: Comparison With the Tribochemistry Of Zndtp Filmsmentioning
confidence: 99%